How satisfied are international students in Malaysia's public universities? An empirical study on student accommodation facilities / Abdulmalik Adozuka Aliu and Nor Rima Muhamad Ariff - Aliu, Abdulmalik Adozuka; Muhamad Ariff, Nor Rima (2018)
The importance of student accommodation on the academic performance of students have been widely recognised. As a result of the rise in global demand for international education, student accommodation have met with new issues such as inadequate accommodation facilities. Hence the need to enhance student satisfaction with accommodation facilities arises in order to attract international students into the universities. Also, whilst some studies have been carried out on student accommodation, there have been little empirical investigation into student accommodation satisfaction with regards to international students, particularly in Malaysia. The paper explores the satisfaction of international students with accommodation facilities. Data was retrieved through a self-administered questionnaire from 253 respondents in three selected public universities in Malaysia. The data which comprises of satisfaction dimensions that includes accommodation unit, support services and social characteristics were subjected to descriptive statistical analysis. Generally, international students were satisfied with the provided accommodation facilities, but expressed a relatively low satisfaction level in items that includes; common and recreation room, pantry (kitchenette), and internet facility. A regression analysis further revealed that all satisfaction dimensions adopted for this study are significant in influencing overall satisfaction of international students with social characteristics the most important. This study points out the need for the provision of adequate and quality accommodation facilities which may serve as a tool for attracting more international students into universities in Malaysia and thereby increasing the reputation of Malaysia's universities to be among the top destinations for international students. This study has shed new insight into international students' perspective of accommodation facilities which will assist the relevant authority, management and facility managers in further improving facilities and services in the students' accommodation.